Understanding Role Expectations in High School Students' Readiness for Family Life: Pemahaman Harapan Peran dalam Kesiapan Siswa SMA untuk Kehidupan Keluarga - F.A. Akramova (Universitas Muhammadiyah Sidoarjo, 2023)
This article aims to investigate the psychological features of high school students' readiness for family life by analyzing the results of the